2010
DOI: 10.3390/medicina46080074
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hemodialysis dose and frequency on survival of patients on chronic hemodialysis in Lithuania during 1998–2005

Abstract: Summary. Introduction. The question of the targets of dialysis dosing remains controversial since the beginning of the long-term dialysis treatment era. It is still uncertain if higher dialysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 14 publications
1
22
0
2
Order By: Relevance
“…Nonetheless, this study underscores the potential risks of twice‐weekly dialysis in patients with minimal RKF. This is consistent with other studies showing increased mortality with twice‐weekly dialysis when RKF is not incorporated into the prescription …”
Section: Rkf Measurementsupporting
confidence: 93%
“…Nonetheless, this study underscores the potential risks of twice‐weekly dialysis in patients with minimal RKF. This is consistent with other studies showing increased mortality with twice‐weekly dialysis when RKF is not incorporated into the prescription …”
Section: Rkf Measurementsupporting
confidence: 93%
“…On the other hand, several contradictory studies indicated that patients on thrice‐weekly HD had a better survival than those on twice‐weekly dialysis (). In an observational study of 2428 patients, less frequent HD was associated with shorter patient survival; weekly treatment time of less than 8 hours was an independent risk factor (). Interestingly, the author did not provide a relative risk analysis for the 12 hours threshold which was considered as the standard weekly duration for thrice‐weekly HD.…”
Section: Effect Of Twice‐weekly Dialysis On Mortalitymentioning
confidence: 99%
“…Similarly, the US Registry data from 1999 (42) reported a survival advantage for twice-weekly hemodialysis, but again, the twice-weekly group had greater RRF. On the other hand, studies from Sudan and Lithuania reported lower survival with less frequent HD (43,44). This could be explained by observations in a recent US cohort which showed that the higher mortality in twice-weekly HD was limited to patient with inadequate RRF (45).…”
Section: Patient Survivalmentioning
confidence: 99%